Ecological Study of Desert Soils of Churu, Rajasthan-Phosphorus Status - Sharma, B.M. (Journal of Soil and Water Conservation, 2022)
Phosphorus status of the desert soils of Churu, Rajasthan has been discussed in the paper. The climate of the area is arid chara-cterized by drought. One hundred and fifty soil samples from thirty soil profiles located on the sandy plains, dunes and depressions were examined for the phosphorus content. Plant communities at the various sites were also noted. The investigation reveals that the phosphorus content ranges from 0.0625 to 0.1124 m.c. per cent. No correlation could be established between the phosphorus content with depth.